Análisis hidrológico de la cuenca del río Toyogres utilizando el modelo HEC-HMS - Umaña-Quirós, Braulio Enrique (Instituto Tecnológico de Costa Rica, 2014)
This report presents the application of the hydrologic model HEC-HMS for the analysis of the watershed of the Toyogres River located in Cartago, Costa Rica. The watershed of the Toyogres River represents a relevant study case because is part of the Cartago’s town. The basin area is 12,27 km2 of which approximately 40% is impervious, with an average slope of the 17%. In the north part the predominant land use is the agricultural cultivation, while in the south part concentrated the urban area. In the model’s calibration process were used 10 rainstorms occurred between September and October 2011. Meanwhile, in the validation process 5 rainstorms recorded between October and November 2011 were used. Nine stages of operation were evaluated due of the combination of three loss models and three transform methods. The most satisfactory results were obtained for the C2 (composed for the Curve Number of the SCS loss model and the Snyder’s Unit Hydrograph transform method) with an average NS efficiency of 0,75 ± 015 in calibration and 0,81 ± 0,10 in validation. For the sensitivity analysis was used only the stage C2. The sensibility is dominated in this case by the curve number parameter, while the initial abstraction was the more insensitive. It is concluded that there is no unique set of optimum parameters, because they are related with the features of the rainstorms as well as the antecedent soil moisture conditions.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2014.
Keywords: Hidrología; Modelación; Calibración; Validación; Filtración